2016
DOI: 10.1038/srep34057
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding reveals that the common cupped oyster in Taiwan is the Portuguese oyster Crassostrea angulata (Ostreoida; Ostreidae), not C. gigas

Abstract: The Pacific cupped oyster, Crassostrea gigas, is one of the major aquacultural shellfish species that has been introduced to Europe and America from its native source in the West Pacific. In Taiwan, the cultivated cupped oysters along the west coast have been identified as C. gigas for over centuries; however, several molecular phylogenetic studies have cast doubt upon the existence of this species in Taiwan and adjacent waters. Indeed, our analyses of mitochondrial cytochrome oxidase I (COI) sequences from 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…Thus, our results suggested that a demographic expansion event occurred recently in C. angulata. This is in agreement with the results of Hsiao et al (2016) who suggested that C. angulata in Asia experienced a sudden population expansion after the last glacial maxima. However, the results from Tajima's D, Fu's F and R 2 tests obtained in the present study and in other studies have to be considered cautiously since the coalescent model used may be inappropriate for highly fecund species such as C. angulata (Steinrucken et al 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, our results suggested that a demographic expansion event occurred recently in C. angulata. This is in agreement with the results of Hsiao et al (2016) who suggested that C. angulata in Asia experienced a sudden population expansion after the last glacial maxima. However, the results from Tajima's D, Fu's F and R 2 tests obtained in the present study and in other studies have to be considered cautiously since the coalescent model used may be inappropriate for highly fecund species such as C. angulata (Steinrucken et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Moehler et al (2011) and Lallias et al (2015) reported nucleotide diversity values of 0.0044 and 0.0046 for C. gigas, respectively, with samples mainly collected in Europe but also in Canada and Japan. Hsiao et al (2016) found haplotype and nucleotide diversities (using mitochondrial cytochrome oxidase I sequences) in Asia being considerably higher in C. angulata than in C. gigas. This suggests that the number of C. angulata individuals introduced into the NE Atlantic must have been sufficiently high to reflect the genetic diversity of C. angulata in its native range.…”
Section: Discussionmentioning
confidence: 80%
“…Recent studies have shown that this species is widely distributed in Asian seas where it shows a high genetic diversity ( Wang et al. 2010 ; Sekino and Yamashita 2013 ; Zhong, Li, Yu, et al 2014 ; Hsiao et al. 2016 ), and also suggested a more complex history of transfers between Asia and Europe ( Grade et al.…”
Section: Introductionmentioning
confidence: 99%
“…and C. angulata (Lam. ) are the most important cultured oyster species at a global level (Buestel et al, 2009;Hsiao et al, 2016), and hold major ecological (Grabowski et al, 2012) and socio-economic importance (FAO, 2015). However, these species present different ecophysiological traits (e.g.…”
Section: Introductionmentioning
confidence: 99%